A new reconfigurable parallel mechanism using novel lockable joints for large scale manufacturing. (August 2023) - Zhao, Yanqin; Jin, Yan; Anderson, Harry; Higgins, Colm
Highlights: A new spherical lockable joint is proposed. Three locking methods are introduced for the lockable joint. A new reconfigurable parallel mechanism (RPM) with large workspace is proposed. Reconfigurable manufacturing systems are introduced using the new RPMs. A reconfiguration strategy is formulated and discussed. Abstract: A new lockable spherical joint is proposed in this paper, and it can be used as a revolute joint, a universal joint or a spherical joint. Three locking methods are introduced to construct the lockable spherical joint. Based on the proposed lockable spherical joint, a new reconfigurable parallel mechanism (RPM) with large positioning workspace is presented. The RPM has a tripod architecture with a lockable joint in each limb, which enables it three types of parallel mechanisms in six motion cases. Mobility analysis of the six motion cases is conducted. The new RPM can realize both translation and rotation by changing operative modes, which can be employed as machine tools, fixtures or manipulators. Based on the new RPM, two modular reconfigurable manufacturing systems are designed for aircraft assembly production, and a reconfiguration strategy is presented.